Let f(x) be the function . Then the quotient can be simplified to for: a= _____ & b= _____
you may have "stumbled" onto the correct constants, but this is incorrectalright so then ( (1) / 16(h+16) ) / h = ( (1) / (16h+265) ) / h = (16h+256)^-1 / h , so to answer my question a= 16 & b=256
$\displaystyle \frac{1}{h} \left(\frac{1}{h+16} - \frac{1}{16}\right)$
$\displaystyle \frac{1}{h} \left(\frac{16}{16(h+16)} - \frac{h+16}{16(h+16)}\right)$
$\displaystyle \frac{1}{h} \left(\frac{16 - h - 16}{16(h+16)}\right)$
$\displaystyle \frac{1}{h} \left(\frac{ -h}{16(h+16)}\right)$
$\displaystyle \frac{ -1}{16(h+16)}\right) = \frac{-1}{16h + 256}$